An investigation into teaching quality in the study centres of the professional accounting bodies in Nigeria - Agunbiade, Abiodun I.; Onuka, Adams O.U.; Akorede, Sherifat F. (Journal of Management and Business Education, 2025)
This study investigated the teaching quality of the tutors in the study centres of the of the professional accounting bodies in Nigeria. The study’s purpose was to assess tutors’ course mastery, pedagogical quality, use of teaching tools, and assessment practices of the tutors in the study centres of the two professional accounting bodies. The research adopted a descriptive survey design. The population comprised student accountants from Lagos and Abuja, two areas selected to represent Southern and Northern Nigeria due to their high concentrations of study centres. A sample of 137 students (91 ICAN and 46 ANAN) was selected through convenience sampling. Data were collected using the Teaching Quality Rating Scale (TQRS), a 4-point scale adapted from Babajide et al. (2015), Validity was confirmed through expert review, and a pilot study with a reliability coefficient of 0.93 determined using Ordinal Alpha. Frequency counts and percentages were used for the analysis of the descriptive data while independent sample t-test was used to test the hypotheses of the study. The findings showed no significant differences between ICAN and ANAN tutors in terms of course mastery, pedagogical quality, use of teaching tools, or assessment practices, suggesting consistent teaching standards across the two bodies. The study concludes that ICAN and ANAN tutors demonstrate a comparable level of quality in the four teaching dimensions assessed. It was recommended plans should be put in place to allow students accountants provide feedback on the instructional delivery of their tutors allowing for improvements that further engage students and enhance learning outcomes.